Trichoderma spp. evaluation, disinfestation and soil chiseling in alfalfa - Rodríguez-Díaz, Dora Acela; Samaniego-Gaxiola, José Alfredo; Gallegos-Robles, Miguel Ángel; Vázquez-Vázquez, Cirilo; Pedroza-Sandoval, Aurelio; Chew-Madinaveitia, Yasmin (Revista Mexicana de Ciencias Agrícolas, 2025)
Crops of alfalfa Medicago sativa L. are limited by crown rot (Rhizoctonia solani), Texas root rot (Phymatotrichopsis omnivora) and soil salinity and compaction. To attenuate crop rots, the objectives were, at the laboratory level, to evaluate methods of inoculation of Trichoderma spp. in alfalfa seed and in the field, to evaluate agronomic parameters, crown rot and Texas root rot after inoculating the seed with T. harzianum (T), deep soil chiseling (C) and reductive soil disinfestation (D), the combinations C+T, C+D, D+C+T, and uninoculated seed and untreated soil as the control (Co). Dishes (PDA) of T. harzianum of 1, 2, 4, 8 and 10 d of growth were used to place previously germinated (GS) or non-germinated (NGS) alfalfa seeds; after 17 d, the size and survival of the NGS seedlings was greater than their corresponding GS (Tukey p< 0.05). In the field, the weight and size of D+C+T vs. Co plants were between (27-35) and (9-3)% higher, respectively, but without statistical significance. Only in the first sampling, a 30% higher yield of D+C+T was detected when compared to Co (Tukey p= 0.05). The quality, yield and plants per m2 of alfalfa were similar to what had been previously reported.